HUBUNGAN SELF-REGULATED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Anggraini, Widia; Widya Sari, Winda (UNIVERSITAS TANJUNGPURA, 2025)
This study aims to determine the relationship between self-regulated learning and students' mathematical creative thinking skills. This study has independent variables and dependent variables, namely self- regulated learning and mathematical creative thinking skills. This study is a quantitative study. The sample of the study was grade IX-A students of SMPN 9 Pontianak. The number of samples in this study was 31 students. Independent learning was measured by an independent learning questionnaire based on the theory of Lestari and Yudhanegara. Data on students' mathematical creative thinking skills were obtained based on a creative thinking ability test on fraction material. The data analysis technique used was Spearman's rank correlation analysis with a significance level of 0.05. This study produced a correlation coefficient (r = 0.787) with p = 0.000, because the significance value is smaller than the error level (p